Virtue, Objectivity, and the Character of the Education Researcher - Burns, David P.; Piquette, Colin L.; Norris, Stephen P. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2009)
In his 1993 book, Hare asks “What Makes a Good Teacher?” In this paper we ask, “What makes a good education researcher?” We begin our discussion with Richard Rudner's classic 1953 essay, The Scientist Qua Scientist Makes Value Judgments, which confronted science with the internal subjectivity it had long ignored. Rudner's bold claim that scientists do make value judgments as scientists called attention to the very foundations of scientific conduct. In an era of institutional research ethics, like the Tri-Council’s ethics policy, Rudner's call for an approach to these value judgments is even more relevant. The contemporary education researcher primarily engages with ethics procedurally, which provides a certain level of consistency and objectivity. This approach has its roots in principle-based theories of ethics that have long been dominant in Western universities. We argue that calls, like Rudner's, for an objective science of ethics, are at the root of this dominant institutional approach. This paper critiques the suitability of such principle-based ethics for solving Rudner's concerns, and posits that educational research ethics is better understood as a matter of character and virtue. We argue that, much like the ethical teacher, the ethical education researcher is a certain kind of person.